(3GdOSJhQ aj GdYdGL GdHOFis - (3OGhO Hf CHj GdHjGf , OGhO Hf SdjeGf Hf GSQGFjd Hf SdjeGf Hf eHGQc GdGSQGFjdj, CHh GdaUd,J (B634 (3g` s ((3GdMGL CMeO ? s)
(3ChdgG (B:s
(3CeG HYO , agPG OSJhQ eSJfHW ef UfGYI GdMceGA GdeYJeO YdjgG ai cJHge GdeYJeHQI s
(3BNQgG (B:s
(3hjbGd fGWd , GKfG YTQ eKbGdkG , hgh ChbjI hfUa , hgh SJg YTQ OQgekG EdG KdK , cjdG hGddg GYde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B136s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B85 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B753s
Keywords: (3GdWHs